2006
DOI: 10.1111/j.1600-0838.2006.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic ankle bracing reduces rearfoot motion during sudden inversion

Abstract: The purpose of this study was to evaluate the effects of ankle bracing on rearfoot angular displacement and angular velocity during a sudden inversion movement. A 1 x 3 factorial design was used. The single independent variable was ankle brace condition with three levels: semi-rigid, lace-up and control. The two dependent variables were rearfoot average angular displacement and average angular velocity. Twenty-four healthy volunteers participated in this study. A motion analysis system was used to capture, mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 39 publications
(49 reference statements)
4
21
1
Order By: Relevance
“…The reduction for the peak inversion velocity was similar, with values of 38%, 23%, and 20%. The results are in agreement with the inversion ROM reduction 7,11 and velocity reduction 7 previously reported in literature. The results from this study further demonstrated that the Element brace was effective in resisting a sudden inversion perturbation and supported the hypothesis of the study.…”
Section: Lateral Cutsupporting
confidence: 82%
See 2 more Smart Citations
“…The reduction for the peak inversion velocity was similar, with values of 38%, 23%, and 20%. The results are in agreement with the inversion ROM reduction 7,11 and velocity reduction 7 previously reported in literature. The results from this study further demonstrated that the Element brace was effective in resisting a sudden inversion perturbation and supported the hypothesis of the study.…”
Section: Lateral Cutsupporting
confidence: 82%
“…Anatomical reflective markers were used to define joint centers and placed at the left and right anterior superior iliac spines, superior iliac crests, posterior superior iliac spines, and greater trochanters, and right femoral epicondyle, right medial and lateral malleoli, and the right first and fifth metatarsal (eg, landing 21,25,32,33 and lateral cut 6,18,28 movements), during which ankle sprains typically occur. More recently, Cordova and colleagues 7 showed that a semirigid ankle brace is more effective in reducing rearfoot angular displacement and velocity than a lace-up brace, but the lace-up brace was more effective than no brace. A few studies examining lateral cutting with ankle braces have focused only on performance, 26 kinematic restrictions, 18,28 or ground reaction force (GRF), and electromyography.…”
Section: Participants Amentioning
confidence: 99%
See 1 more Smart Citation
“…However, investigations 26-29 of 3-dimensional motion analysis consistently showed higher peak angular velocities in trials of running, cutting, and jump landings when sprains occurred. We did not test angular velocities in the present study; however, Cordova et al 30 and Tang et al 31 demonstrated reduced angular excursion and velocity during inversion triggered by a tilting platform in participants wearing a semirigid ankle brace compared with those wearing a lace-up brace and control conditions. The more pronounced stabilization effect of the hinged Ankle X model and the nonhinged model might be due to their design, which encompasses the ankle more than the hinged Embrace model does; the latter has a narrower plastic stirrup at both sides of the ankle.…”
Section: Discussionmentioning
confidence: 66%
“…In order to prevent ankle sprain injury, taping and bracing are commonly used by athletes (Cordova et al, 2007). However, these methods restrict the freedom of ankle joint motion and hence affect the performance in sports (Hume & Gerrard, 1998).…”
Section: Introductionmentioning
confidence: 99%